Shaping the world of work - time for a UK jobs strategy - Sisson, Keith (Coventry, 2016)
"The approach to employment poses one of the UK government’s biggest post-Brexit challenges. Brexit is accepted as exposing widespread anger and dissatisfaction with wages, living standards and their inequality. The new Prime Minister seems sensitive to the implications. In her maiden speech, she talked about dealing with work-related ‘injustices’. She also touched on people’s worries about job security, the cost of living and paying the mortgage. Her mission, she said, was to give people more control over their lives and ‘make Britain a country that works not just for the privileged few, but that works for every one of us’. Her proposals, which include putting workers on the board and developing an industrial strategy, are important in recognising the need for an active as opposed to passive government role in shaping the world of work. They aren’t going to be enough on their own, however, to deal with the low pay, low skill and low productivity at the heart of the UK’s problems, let alone the challenges digitalisation poses. There needs to be a jobs strategy with a clear focus, appropriate institutional framework and mutually reinforcing policies. This paper makes ten suggestions for what might be involved."